PENGEMBANGAN KETERAMPILAN PROSES SAINS SISWA MENGGUNAKAN METODE INKUIRI TERBIMBING BERBASIS PORTOFOLIO SISWA SMA NEGERI 1 PURBOLINGGO - Triana Asih (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
Biology learning should emphasize the provision of direct experience and at this time, using idelly scinence process skills (SPS). But on the subject of research, the lack of provision direct experience during the learning process and there is no provision of SPS in a structure way. Thus, the research applied the method of an inquiry guided based-portfolio, a method own answer to exsiting problems by using sins process skills. The conclusions in this study is the application of an inquiry guided based-portfolio to develop students scinence process skills classes X4 semsester odd Sinior High School 1 Purbolinggo year 2011/2012. The development can be observed from the increase as follows: the skills to make hypothesis or pre-CAR by 6,5% to 72,4% after the study, acquire skill and process data from the pre-CAR by 48,8% after the study to 80,6%, communicating skills pre-CAR by 6,5% after the study to 82%, and concluded at a rate skills of pre-CAR by 9,8% after the study to 78,7%.Kata kunci: Inkuiri Terbimbing, Portofolio, Keterampilan Proses Sains